Potency Of Clitoria Ternatea As Forage For Livestock - Sutedi, Endang (Indonesian Animal Sciences Society, 2013)
Availability of forage is one of the factors determining the success of ruminant livestock production, especially during drought that resulting in poor livestock condition. Forage legume is an important group of forage plants, containing high nutritive value. One of the legume plants which potential as ruminant feed is Clitoria ternatea. This plant can grow well in all types of soil and dry conditions, also produces seed continously. The production of forage was 25-29 ton DM/ha with seed production was 2.2 ton DM/ha per harvest (42 day cutting interval). The crude protein and crude fiber contents of C. ternatea leaf were 21.5 and 29%, respectively. Meanwhile, the crude protein, crude fat and sugar contents of C. ternatea seed were 25-38,10 and 5%, respectively. This plant can be fed to ruminant as fresh forage or hay with no negative effect on growth performance of animal. The average daily gain of cattle grazing on mixture of Brachiaria mutica grass and C. ternatea was 680 g/day. The value of DM and OM digestibilities of C. ternatea in cattle were 50.15 and 53.47%, respectively. Feeding C. ternatea to dairy cow impoved the content of fat and total solid of milk, meanwhile feeding it to male sheep improved quality of semen.Key words: Clitoria ternatea, animal feed